Identification of Common Hub Genes in Human Dermal Fibroblasts Stimulated by Mechanical Stretch at Both the Early and Late Stages - Dong, Chen; Liu, Wei; Zhang, Yu; Song, Yajuan; Du, Jing; Huang, Zhaosong; Wang, Tong; Yu, Zhou; Ma, Xianjie (Frontiers in Surgery, 2022)
Background: Mechanical stretch is vital for soft tissue regeneration and development and is utilized by plastic surgeons for tissue expansion. Identifying the common hub genes in human dermal fibroblasts (HDFs) stimulated by mechanical stretch at different stages will help elucidate the mechanisms involved and improve the efficiency of tissue expansion. Methods: A gene expression dataset (GSE58389) was downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) in HDFs between cyclic mechanical stretching and static samples were identified at 5 h and 24 h. Common DEGs overlapped in both the 5 h and 24 h groups. GO) and KEGG pathway enrichment analyses were performed to determine the functions of the DEGs. Protein-protein interaction networks were constructed using the STRING database. The top 10 hub genes were selected using the plug-in Cytohubba within Cytoscape. The regulatory network of hub genes was predicted using NetworkAnalyst. Results: A total of 669 and 249 DEGs were identified at the early (5 h) and late stages (24 h), respectively. Of these, 152 were present at both stages and were designated as common DEGs. The top enriched GO terms were “regulation of autophagy” at the early stage, and “sterol biosynthetic processes” at the late stage. The top KEGG terms were “pyrimidine metabolism” and “synaptic vesicle cycle” at the early and late stages, respectively. Seven common DEGs DDX17, EXOC7, CASKIN1, RAVER1, LCE1D, LCE1C, and PKD1 and three common DEGs (XRN2, TCP1, and STX3) were shown to be upregulated and downregulated hub genes, respectively. The GO terms of the common hub genes were “skin development” and “mRNA processing.” After constructing the regulatory network, hsa-mir-92a-3p, hsa-mir-193b-3p, POLR2A. SMAD5, and MAZ were predicted as potential targets in both stages. Conclusion: At the early stage, there were clear changes in gene expression related to DNA and chromatin alterations; at late stages, gene expression associated with cholesterol metabolism was suppressed. Common DEGs related to skin development, transcriptional regulation, and cytoskeleton rearrangement identified in both stages were found to be potential targets for promoting HDF growth and alignment under mechanical stretch.